2020
DOI: 10.1021/acscatal.0c03475
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic Study of Polyol Hydrodeoxygenation over a Bifunctional Pt-WOx/TiO2 Catalyst

Abstract: In recent years, metal−metal oxide catalysts have proven to be robust catalysts for hydrodeoxygenation (HDO) of oxygenated compounds derived from biorenewable feedstocks to value-added products. Herein, the conversion of 1,2,6-hexanetriol (1,2,6-HT) to 1,6-hexanediol (1,6-HD) in aqueous media over a Pt-WO x /TiO 2 catalyst is examined via isotope incorporation in HDO of a model compound, 1,2-pentanediol (1,2-PD). Absence of a primary kinetic isotope effect (k H /k D = 0.84 ± 0.11) disproves a potential direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…Here, metal V could combine with oxygen to form a variety of different metal oxides, and the lower-valence V 3+ possessed a stronger oxyphilic ability to generate more oxygen vacancies. Apparently, more V 3+ was formed in the modified catalyst, thereby enhancing its adsorption and deoxygenation activity for oxygenated compounds . On the other hand, the O 1s spectra also showed that more oxygen vacancies were obtained in modified catalysts.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, metal V could combine with oxygen to form a variety of different metal oxides, and the lower-valence V 3+ possessed a stronger oxyphilic ability to generate more oxygen vacancies. Apparently, more V 3+ was formed in the modified catalyst, thereby enhancing its adsorption and deoxygenation activity for oxygenated compounds . On the other hand, the O 1s spectra also showed that more oxygen vacancies were obtained in modified catalysts.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Apparently, more V 3+ was formed in the modified catalyst, thereby enhancing its adsorption and deoxygenation activity for oxygenated compounds. 55 On the other hand, the O 1s spectra also showed that more oxygen vacancies were obtained in modified catalysts. The binding energies at 530.1, 531.1, 532.3, and 532.9 eV were ascribed to the lattice oxygen, less charged O anions ( I O), dissociatively chemisorbed O species ( II O), and SiO 2 , respectively, noting that I O was generally considered to be the indicators of surface oxygen vacancies.…”
Section: Methodsmentioning
confidence: 98%
“…Additionally, it is assumed that in H 2 -deNO x some hydrogen spillover from Pt to adjacent W = O species, evidenced by LSR (Fig. 3), can occur increasing the number of W-OH Bronsted acid sites in proximity of the Pt particles [44,45]. From the discussion of above deNO x and TPD studies as well as the cited literature it is drawn the conclusion that amonium species, formed at the interface of Pt and the WO x /Al 2 O 3 /SiO 2 support, may react with NO likely adsorbed on Pt to yield N 2 and H 2 O.…”
Section: Resultsmentioning
confidence: 99%
“…Stephens and co-workers reported a mechanistic study of the conversion of 1,2,6-HT to 1,6-HD over Pt-WO x /TiO. Using D 2 and H 2 , the hydroxyl group on C2 was dehydrated, resulting in carbocation via W-OH species, and thereafter, W-O-acquired the hydrogen atom on C1 to form an aldehyde, which interacted with D 2 to form 1,6-HD (Stephens et al, 2020). Noble metals have a high hydrogen dissociation capacity and reduce metal oxides to metal hydroxides or create oxygen vacancies to catalyze the dehydration of hydroxyl groups.…”
Section: Straight Chain Diol Productionmentioning
confidence: 99%
“…Noble metals have a high hydrogen dissociation capacity and reduce metal oxides to metal hydroxides or create oxygen vacancies to catalyze the dehydration of hydroxyl groups. As a result, the design of catalysts, with metal oxidation and noble metals, has emerged as a prominent strategy for the selective cleavage of C-OH (Guan et al, 2020;Stephens et al, 2020).…”
Section: Straight Chain Diol Productionmentioning
confidence: 99%